Presidencialismo y Monarquía: ocaso y similitudes - Mercado Maldonado, Asael; Olvera García, Jorge; Olvera Herreros, Omar (Nómadas. Critical Journal of Social and Juridical Science, 2011)
Trough the modern history of democracy, and since Charles de Secondat wrote his work L’espirit des lois in 1748 in which he express the powers separation theory, remarkable authors have been working on consecrating this theory on an ideal government form, which the liberal theory saw consolidated on the presidential form shaped on the United States of America federal constitution of 1787. Montesquieu wrote his work, moments on which monarchic regime was on evident risk because of the growth of English parliament and the consolidation of parliamentarism way of government, motive enough to shape a new government form which maintains, at least moderately, the privileges of the crowned favored elites, this is how presidentialism it’s conceived.